CYBERBULLYING DALAM PERSPEKTIF HADIS: LARANGAN MERENDAHKAN, MENCELA, DAN MEMBUKA AIB DI RUANG DIGITAL - Evi Aulia; Muhammad Jiddan Alamsyah (DIRAYAH : Jurnal Ilmu Hadis, 2026)
The development of information technology in the 21st century has given rise to the phenomenon of cyberbullying as a form of digital-based violence that has serious impacts on the honor and psychological health of individuals. Although this term is relatively new, its moral substance is closely related to the prohibitions on backbiting, namimah, istihzā’, and revealing shame in the Prophet's hadith. The urgency of this research lies in the need to formulate a normative basis for hadith that is relevant in responding to the ethical problems of contemporary digital communication. This research aims to analyze hadiths on the protection of honor and the prohibition of revealing shame and reconstruct them as the foundation of Islamic digital ethics. This research is a library research study with a hadith science approach through the stages of takhrij, sanad criticism, and thematic analysis of matan (maudhu‘i), and uses the maqāṣid al-syarī‘ah framework, especially the principle of ḥifẓ al-‘irḍ. The results of this study indicate that the hadith not only prohibits insults and exposure of shame in traditional social contexts, but also provides normative principles that can be actualized in the digital space, including prohibitions on doxing, the unauthorized distribution of private content, and derogatory speech on social media. This study contributes to strengthening the study of hadith dirayah in the contemporary context by offering a synthesis between the methodology of hadith criticism and the reconstruction of digital communication ethics based on maqāṣid.